Assistance in Calculating Cost of Goods Sold (HPP) at UMKM Penyetan Hot Nyot in Dadirejo Village, Pekalongan - Nana Raudhotul Janah; Dwi Suci Anggraeni; Ana Kharisma Silviya; Ade Gunawan; Ria Anisatus Sholihah; Hendri Hermawan Adinugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Small and medium-sized enterprises (SMEs) in Dadirejo Village, Pekalongan, will receive support and training on financial reporting. Financial records are expected to provide knowledge of accounting, in particular calculating the price of sales items and using them in accordance with the Financial Accounting Standards. All of these communal devotions are held in one place, namely in the Hot Nyot dining room, on May 23, 2024. The implementation of this activity is in the form of accompanying and training the price calculation of goods of sale (HPP) for the seller of the dining house. Surveys (for planning), implementation (for interviews and observations), and evaluation are the processes used. The result of this community service activity is that the UMKM supporter of the Hot Nyot Dining Shop needs an accompaniment to record the financial reports. It is important to improve their knowledge and skills in accounting, especially the calculation of sales commodity prices (HPPs) in accordance with the Financial Accounting Standards, as well as teaching them online marketing strategies. The evaluation results showed a significant improvement in the ability to determine appropriate selling prices and use information technology to increase market share. Thus, this addition is expected to help UMKM achieve optimal profitability and sustainability.